A comprehensive exploration of the genetic legacy and forensic features of Afghanistan and Pakistan Mongolian-descent Hazara. (September 2019) - He, Guanglin; Adnan, Atif; Rakha, Allah; Yeh, Hui-Yuan; Wang, Mengge; Zou, Xing; Guo, Jianxin; Rehman, Muhammad; Fawad, Abulhasan; Chen, Pengyu; Wang, Chuan-Chao
Highlights: Indel resource is provided for Central/South Asian Hazara and Chinese Bouyei. Investigator ® DIPplex panel is informative in Mongolian-descent Hazara. Four datasets reveal genetic affinity between Hazaras and Turkic speakers. East-West Eurasian admixed genetic profile is found in Hazaras. qpAdm reveals 57.8% Mongolian-related ancestry in Hazara. Abstract: Afghanistan and Pakistan are rich with a complex landscape of culture, linguistics, ethnicity and genetic legacy at the crossroads between Indian-Subcontinent and Central Asia. Hazara people have historically been suggested to be Mongolian decedents but seldom been genetically studied. To dissect the genetic structure and explore the forensic characteristics of Hazara people, we first genotyped 30 Insertion/deletion (Indel) markers in 468 samples from 2 aboriginal Hazara populations from Afghanistan and Pakistan, and 100 East Asian comparative Bouyei samples using the Investigator® DIPplex kit. Subsequently, we carried out a comprehensive population genetic analysis from four different datasets: 8895 30-Indel genotype data from 51 populations, 15, 895 30-Indel allele frequency data from 98 populations, 1048 genotypes of 993 STRs and Indels from 53 HGDP populations and 2068 whole-genomes (621, 799 single nucleotide polymorphisms) from 165 worldwide Human origin reference populations, to further unravel the genetic complexity between Hazara and worldwide human populations using various statistical analysis. We find that 30 Indels are in accordance with HWE, and informative and polymorphic in both Central Asians Hazara and East Asian Bouyei populations. The forensic combined probability of exclusion is larger than 0.9943 and the cumulative power of discrimination is larger than 0.99999999999936. These forensic parameters show the high level of diversity, which makes the Indel amplification system suitable for forensic routine work and may be used as a supplementary assay for routine forensic investigation. The results from pairwise genetic distances, MDS, PCA, and phylogenetic relationship reconstruction demonstrate that present-day Hazaras are genetically closer to the Turkic-speaking populations (Uyghur, Kazakh, and Kyrgyz) residing in northwest China than with other Central/South Asian populations and Mongolian. Outgroup and admixture f 3, f 4, f 4 -ratio, qpWave, and qpAdm results further demonstrate that Hazara shares more alleles with East Asians than with other Central Asians and carries 57.8% Mongolian-related ancestry. Overall, our findings suggest that Hazaras have experienced genetic admixture with the local or neighboring populations and formed the current East-West Eurasian admixed genetic profile after their separation from the Mongolians.